Molecular epidemiology of bacterial enteric pathogens associated with diarrhea in children under 5 years of age in Lagos State, Nigeria. - Ezioma, Dike Adobi; Omosigho, Pius Omoruyi; Sulaiman, Giwa; Bridget, Omene Ogheneakporobo; Eze, Glory Obiageli; Omoruyi, Ewean chukwuma; Okesanya, Olalekan John (Australian Journal of Medical Science, 2025)
Infectious diarrhea remains a widespread, contagious illness, posing severe challenges in developing countries. The aim of the study is to determine the molecular epidemiology of bacterial enteric pathogens associated with diarrhea in children under five years in Lagos State. A total of 268 participants were recruited for this study. Fresh stool samples were collected in sterile, DNase-free containers, and samples were stored at -80°C and analysed using the multiplex quantitative PCR (qPCR) method utilising a fluorescent probe. The study found that E. coli (EPEC) was the most frequently detected pathogen in children, found in 34.0%, followed by Campylobacter jejuni (18.2%). Co-infections involving both pathogens were recorded in 5.7% of participants. No cases of Salmonella, Shigella, Vibrio cholerae, or Aeromonas spp. were found, suggesting possible regional pathogen shifts or the effectiveness of local public health measures. The highest prevalence of all three bacterial infections was observed in infants aged 0-1 years, indicating increased vulnerability. Gender analysis showed near-equal E. coli (EPEC) infection rates between males and females, but the difference was statistically significant. Urban areas had the highest burden of infections across all bacterial types, followed by semi-urban areas, while rural areas reported the fewest cases. E. coli (EPEC) was most prevalent among children using borehole and tap water, with Campylobacter jejuni significantly associated with tap and borehole water use. To reduce diarrhea disease, interventions should prioritise exclusive breastfeeding, safe weaning education, improved water safety, and hygiene promotion through focused maternal and child health programs.